Preserving Cultural Heritage: A Study of Abdygali Sariyev’s Poetic Vision - Almas, Oralbek; P.T., Auyesbayeva; Mambetov, Zholdasbek; Daribaev, Samal; Karbozov, Yerkhan (Journal of Ecohumanism, 2025)
Abdygali Sariyev, a prominent Kazakh poet and writer, stands as one of the most influential literary figures in Kazakhstan’s 20th century. His work is characterized by deep philosophical reflection, a strong connection to Kazakh history and tradition, and a profound exploration of themes such as national identity, freedom, and the relationship between the individual and society. This paper explores the literary legacy of Sariyev by analyzing his most notable works, examining the thematic concerns that pervade his poetry, and evaluating his role within the broader context of Kazakh literature and culture. The methods employed in this study include a qualitative literary analysis, close reading of Sariyev’s works, and historical context evaluation. The paper further explores how Sariyev’s style, language, and imagery reflect both the traditional Kazakh oral poetry and the modernist movements of his time. By situating Sariyev within the cultural and political landscape of Kazakhstan during the Soviet era, this paper sheds light on how his works contribute to the development of Kazakh literature, providing insights into national consciousness and the power of literature to shape collective memory. Through examining primary texts and secondary scholarly interpretations, the study also seeks to highlight the continuing relevance of Sariyev’s poetic vision in post-Soviet Kazakhstan. The research underscores the importance of preserving the literary legacy of poets like Sariyev to understand the rich cultural heritage of Kazakhstan.